2010
DOI: 10.1016/j.ijid.2009.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous meningitis in HIV-infected patients in Brazil: clinical and laboratory characteristics and factors associated with mortality

Abstract: Clinical and laboratory manifestations were unspecific. Disseminated tuberculosis and severe immunosuppression were common. Mortality was high and the 9-month survival rate was low. Tachycardia and prior HAART were associated with death within 9 months of diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 27 publications
3
27
0
1
Order By: Relevance
“…The reports about the characteristic of cerebrospinal fluid cytology (CSFC) in TBM patients were not consistent. [9][10][11][12][13] Some scholars believe a lymphocyte predominance is the typical feature of TBM, while others think the increasing number of neutrophils is the characteristics of TBM. In our study, there were 54% (27 of 50) patients' CSF showed neutrophil predominance (>50%) in TBM group.…”
Section: Discussionmentioning
confidence: 99%
“…The reports about the characteristic of cerebrospinal fluid cytology (CSFC) in TBM patients were not consistent. [9][10][11][12][13] Some scholars believe a lymphocyte predominance is the typical feature of TBM, while others think the increasing number of neutrophils is the characteristics of TBM. In our study, there were 54% (27 of 50) patients' CSF showed neutrophil predominance (>50%) in TBM group.…”
Section: Discussionmentioning
confidence: 99%
“…20 Our low CSF culture yield may reflect antituberculous treatment or the difficulty of culturing Mycobacterium tuberculosis from the CSF especially with HIV co-infection. [21][22][23][24] Direct contiguous spread from infected cervical, mediastinal, or retroperitoneal lymph nodes may provide another route for spinal infection in the absence of bony involvement. This was convincingly demonstrated in only 2 of our cases.…”
Section: Reviewed the Mri Of 55 Hiv-positive European Andmentioning
confidence: 99%
“…Like HIV-1 uninfected patients, HIV-1 infected patients can present with a range of neurological manifestations: tuberculous meningitis (TBM), tuberculomas, radiculomyelitis and tuberculous brain abscess [39]. In patients with TB, meningeal involvement is more common in HIV-1-infected patients [40,41].…”
Section: Asymptomatic Active Pulmonary Tbmentioning
confidence: 99%